1968
DOI: 10.1037/h0026536
|View full text |Cite
|
Sign up to set email alerts
|

Early experience and facilitation of feeding in domestic chicks.

Abstract: Social facilitation of feeding in domestic chicks has been attributed to emotion reduction accompanying social stimuli. In order to test the hypothesis that this emotion reduction is due to socially-raised chicks being imprinted to one another, 3 groups of domestic chicks were imprinted, reared in isolation, or reared in a group. The number of food pecks made in a novel testing area were recorded when each S was alone, with the imprinting object, or with a food-deprived chick. The test condition similar to eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
1

Year Published

1971
1971
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 6 publications
(9 reference statements)
0
9
1
Order By: Relevance
“…Immobility decreases whereas activity and vocalization increase as familiarity with the test situation rises and hence, presumably, lessens fearfulness (Jones, 1977b). Feeding only occurs when fear levels are reduced (Jones, 1977c;Murphy, 1978;Rajecki, Kidd, Wilder, & Jaeger, 1975;Wilson, 1968) and fearfulness is negatively correlated with peck rate (Brown & Kiely, 1974). In this context the present results are wholly consistent with the suggestion that early environmental enrichment decreases fearfulness in fear-inducing situations, that is, reduces the inhibitory effect of fear and allows attempts at feeding and active escape.…”
Section: Discussionmentioning
confidence: 99%
“…Immobility decreases whereas activity and vocalization increase as familiarity with the test situation rises and hence, presumably, lessens fearfulness (Jones, 1977b). Feeding only occurs when fear levels are reduced (Jones, 1977c;Murphy, 1978;Rajecki, Kidd, Wilder, & Jaeger, 1975;Wilson, 1968) and fearfulness is negatively correlated with peck rate (Brown & Kiely, 1974). In this context the present results are wholly consistent with the suggestion that early environmental enrichment decreases fearfulness in fear-inducing situations, that is, reduces the inhibitory effect of fear and allows attempts at feeding and active escape.…”
Section: Discussionmentioning
confidence: 99%
“…Since pecking is such a prevalent behavior in chickens, it is not surprising that research on these animals in the area of social influences on consumption has used the peck as the dependent measure. Studies have consistently shown that socially reared chickens eat more in the company of other chickens than they eat when alone (Tolman, 1968a;Tolman & Wilson, 1965;Wilson, 1968), even when subjects are fed to satiation before the introduction of hungry companions (Bayer, 1929;Fischel, 1927;Katz & Revesz, 1909, cited in Tinbergen, 1951Tolman, 1965).…”
mentioning
confidence: 99%
“…Wilson (1968) has shown that familiar objects in a novel testing area facilitated feeding in domestic chicks, presumably by reducing their fear. Dawson and Siegel (1967) found sex differences in the levels of home-cage resting and body-stretching in White Rock chickens; females rested more than males but stretched less.…”
Section: Discussionmentioning
confidence: 98%